2005
DOI: 10.1167/iovs.05-0132
|View full text |Cite
|
Sign up to set email alerts
|

Drug Intervention Can Correct Subnormal Retinal Oxygenation Response in Experimental Diabetic Retinopathy

Abstract: These results demonstrate, for the first time, that drug treatment can reverse an established subnormal DeltaPo2. Furthermore, this effect could not be predicted by a drugs' ability to prevent the development of subnormal DeltaPo2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 30 publications
4
53
0
1
Order By: Relevance
“…interventionally). Importantly, we found that the success of two drug treatments at correcting abnormal DPO 2 when administered preventatively was not predictive of success when administered interventionally (60). Furthermore, a cyclo-oxygenase-2 inhibitor was found to reverse the abnormal DPO 2 when treatment was started after induction of the diabetes (60).…”
Section: Dpomentioning
confidence: 84%
See 1 more Smart Citation
“…interventionally). Importantly, we found that the success of two drug treatments at correcting abnormal DPO 2 when administered preventatively was not predictive of success when administered interventionally (60). Furthermore, a cyclo-oxygenase-2 inhibitor was found to reverse the abnormal DPO 2 when treatment was started after induction of the diabetes (60).…”
Section: Dpomentioning
confidence: 84%
“…(b) A range of vasoactive drugs, including aminoguanidine, aldose reductase inhibitors, and inducible nitric oxide synthetase and cyclo-oxygenase-2 inhibitors, corrected abnormal retinal DPO 2 in experimental diabetic retinopathy (57,60). (c) Carbogen improves retinal oxygenation relative to pure O 2 breathing (20,61).…”
Section: Dpomentioning
confidence: 99%
“…We found that mice lacking iNos were protected from the diabetes-induced production of nitric oxide, nitration of retinal proteins and, importantly, from the diabetes-induced degeneration of retinal capillaries. Previous research has demonstrated that inhibition of iNOS or iNos deficiency also inhibits development of early functional alterations in retinal oxygenation in diabetes [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen tension (in millimeters of mercury) in phantoms was measured by using an oxygen-sensitive fiberoptic probe (OxyLab; Oxford Q uantitative measurement of Po 2 in vivo could provide a clinically relevant indicator of oxygen concentration in the vitreous and the surrounding tissue, such as the retina, lens, and ciliary body. Abnormal vitreal oxygen tension has been linked to a number of ocular diseases, including cataract, diabetic retinopathy, and central retinal vein occlusion (1)(2)(3)(4). Vitrectomy (1,5) and hyperbaric oxygen therapy (6) have been associated with increased incidence of nuclear cataract, likely related to high vitreal Po 2 and reactive oxygen species contributing to cataract formation (7).…”
Section: Phantom and Ex Vivo Studiesmentioning
confidence: 99%